2014
DOI: 10.1007/s12029-014-9652-5
|View full text |Cite
|
Sign up to set email alerts
|

Serum Chemokine Ligand 5 (CCL5/RANTES) Level Might be Utilized as a Predictive Marker of Tumor Behavior and Disease Prognosis in Patients with Gastric Adenocarcinoma

Abstract: Serum CCL5 levels might be utilized as a predictive marker of tumor behavior and disease prognosis in patients with gastric adenocarcinoma. Further studies to assess tissue expression of CCL5 and its gene polymorphisms are suggested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 15 publications
0
17
0
Order By: Relevance
“…Moreover, CCL5 levels, as well as their changes in liquid biopsy samples, could potentially be useful to monitor or predict disease progress and treatment outcomes. Clinical evidence has revealed that elevated levels of tissue or plasma CCL5 are markers of an unfavorable outcome in patients with breast [ 41 , 42 , 43 , 44 ], cervical [ 45 ], prostate [ 26 ], ovarian [ 46 ], gastric [ 47 , 48 ], colorectal [ 49 ], or pancreatic cancer [ 50 ].…”
Section: Possible Clinical Applications: Ccl5 and Ccr5 As Therapeumentioning
confidence: 99%
See 4 more Smart Citations
“…Moreover, CCL5 levels, as well as their changes in liquid biopsy samples, could potentially be useful to monitor or predict disease progress and treatment outcomes. Clinical evidence has revealed that elevated levels of tissue or plasma CCL5 are markers of an unfavorable outcome in patients with breast [ 41 , 42 , 43 , 44 ], cervical [ 45 ], prostate [ 26 ], ovarian [ 46 ], gastric [ 47 , 48 ], colorectal [ 49 ], or pancreatic cancer [ 50 ].…”
Section: Possible Clinical Applications: Ccl5 and Ccr5 As Therapeumentioning
confidence: 99%
“…While many virulence factors of H. pylori have been described, the CagA (cytotoxin-associated gene A) toxin, which is translocated into gastric epithelial cells via a bacterial secretion system, appears to be the most specific for the development of a pathological phenotype. Infection with H. pylori , a potent activator of NF-κB in gastric epithelial cells, increases CCL5 [ 47 , 81 , 82 , 83 ] and induces the expression of a variety of genes, including IL-1, IL-6, IL-8, IL-10, TNF-α, VEGF, cyclooxygenase-2 (COX-2), inducible nitric oxide synthase (iNOS), cell cycle regulators, the matrix metalloproteinases (MMP)-2, MMP-7, MMP-9, and also adhesion molecules [ 82 , 84 ].…”
Section: Gastric Cancer and Its Tmementioning
confidence: 99%
See 3 more Smart Citations